2003
DOI: 10.1097/01.tp.0000085661.52980.95
|View full text |Cite
|
Sign up to set email alerts
|

C-Jun N-terminal kinase (JNK) inhibitor, SP600125, blocks interleukin (IL)–6-induced vascular endothelial growth factor (VEGF) production: cyclosporine A partially mimics this inhibitory effect

Abstract: Angiogenesis is a common complication of organ-transplant rejection. One of the primary responsible molecules for enhanced angiogenesis is vascular endothelial growth factor (VEGF). Activated protein (AP)-1 is considered to play a key role in the transcription of VEGF. c-jun N-terminal kinase (JNK), one of the MAP kinase family members, plays a critical role in AP-1 activation. Thus, we tested the effect of a novel JNK inhibitor, SP600125, on VEGF production in fibroblasts. SP600125 significantly suppressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 10 publications
3
29
1
Order By: Relevance
“…VEGF is the most powerful regulator of angiogenesis, and plays an important role in the regulation of inflammatory periodontitis (6). Our previous reports have shown that IL-6/sIL-6R induced VEGF secretion in HGFs (18). As shown in Japan and Strategic Medical Science Research Centre from the Ministry of Education, Culture, Sports, Science, and Technology of Japan, 2010-2014.…”
Section: Growth Factors-possible Mechanisms Of Induction Of Angiogenesismentioning
confidence: 86%
See 2 more Smart Citations
“…VEGF is the most powerful regulator of angiogenesis, and plays an important role in the regulation of inflammatory periodontitis (6). Our previous reports have shown that IL-6/sIL-6R induced VEGF secretion in HGFs (18). As shown in Japan and Strategic Medical Science Research Centre from the Ministry of Education, Culture, Sports, Science, and Technology of Japan, 2010-2014.…”
Section: Growth Factors-possible Mechanisms Of Induction Of Angiogenesismentioning
confidence: 86%
“…Both IL-1β and IL-6/sIL-6R increased significantly IL-1ra and MCP-1 ylation of IL-6 signal transducer gp130 in HGFs (19). At least two distinct signaling cascades, the Stat3 and the MAPKs pathways, have been activated and lead to various responses such as VEGF secretion in HGFs (18). In the present study, we demonstrated for the first time that IL-1β but not IL-6/sIL-6R induces gp130 expression in HGFs at mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Cav-1 may co-relate to VEGF in inflamed lesions, leading to angiogenesis. Previously, we have reported that IL-6/sIL-6R promotes VEGF secretion in HGFs, and it is considered that HGFs possess the ability of VEGF production (20). Therefore, we examined whether secreted Cav-1 induces VEGF secretion in HGFs.…”
Section: Angiogenesismentioning
confidence: 96%
“…Fibroblasts such as HGFs are the most abundant cells in gingival connective tissues and play an important role in the control of inflammation (28,29). Recently, we demonstrated that VEGF expression is significantly induced by IL-6 in the presence of sIL-6R in HGFs (20 …”
Section: Cav-1 Induces Mrna Expression Of Various Inflammation-relatementioning
confidence: 99%